An efficient inducible RPE-Selective cre transgenic mouse line. (January 2021) - Chen, Ming; Kim, Lily; Lu, Carolyn W.; Zeng, Hong; Vollrath, Douglas
Abstract: Cre-mediated modulation of gene function in the murine retinal pigment epithelium (RPE) has been widely used, but current postnatal RPE-selective Cre driver lines suffer from limited recombination efficiency and/or ectopic or mosaic expression. We sought to generate a transgenic mouse line with consistently efficient RPE-selective Cre activity that could be temporally regulated. We used ϕC31 integrase to insert a DNA construct encoding a human BEST1 promoter fragment driving a Cre recombinase estrogen receptor fusion ( BEST1-CreERT2 ) at the Rosa26 locus of C57BL/6J mice. Rosa26 BEST1-CreERT2 mice were bred with a tdTomato reporter line and to mice with a Cre-conditional allele of Tfam . 4-hydroxytamoxifen or vehicle was delivered by four consecutive daily intraperitoneal injections. TdTomato was robustly expressed in the RPE of mice of both sexes for inductions beginning at P14 (males 90.7 ± 4.5%, females 84.7 ± 3.2%) and at 7 weeks (males 84.3 ± 7.0%, females 82 ± 3.6%). <0.6% of Muller glia also expressed tdTomato, but no tdTomato fluorescence was observed in other ocular cells or in multiple non-ocular tissues, with the exception of sparse foci in the testis. No evidence of retinal toxicity was observed in mice homozygous for the transgene induced beginning at P14 and assessed at 7–10 months. RPE-selective ablation of Tfam beginning at P14 led to reduced retinal thickness at 8 months of age and diminished retinal electrical responses at 12 months, as expected. These findings demonstrate that we have generated a mouse line with consistently efficient, tamoxifen-mediated postnatal induction of Cre recombination in the RPE and a small fraction of Muller glia. This line should be useful for temporally regulated modulation of gene function in the murine RPE. Abstract : Consistent and robust induction of Cre activity throughout the RPE . RPE-selective inducible Cre activity across a range of postnatal ages . No evidence of retinal toxicity in 7-month-old transgenic homozygotes.